A Task for Sisyphus : Why Europe's Roma Policies Fail - Rostas, Iulius (Book collections on Project MUSE., 2019)
"The book provides answers to the big question that few scholars dare to ask: why policies towards Roma in Europe are failing. After three rounds of policy-making specifically targeting Roma in Europe, it is the time for the academic community to explore the causes of the failure to effectively address the Roma predicament, requiring an interdisciplinary approach. The book analyses the issue from multiple perspectives and disciplines using policy analysis, discourse analysis, and legal analysis. In providing answers to the big question - why policies towards Roma are failing - the author focuses on the policy making process, the construction and categorization of Roma by different actors within this process. Rostas also analyses the policy concepts employed by policy makers over the last twenty-five years, the policy instruments used, and the institutional arrangements that govern the Roma-related issues"--